2019
DOI: 10.1080/15548627.2019.1668228
|View full text |Cite
|
Sign up to set email alerts
|

The Paf1 complex transcriptionally regulates the mitochondrial-anchored protein Atg32 leading to activation of mitophagy

Abstract: Mitophagy is a critical process that safeguards mitochondrial quality control in order to maintain proper cellular homeostasis. Although the mitochondrial-anchored receptor Atg32-mediated cargo-recognition system has been well characterized to be essential for this process, the signaling pathway modulating its expression as a contribution of governing the mitophagy process remains largely unknown. Here, bioinformatics analyses of epigenetic or transcriptional regulators modulating gene expression allow us to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In cells lacking PpSin3 and PpRpd3, PpAtg32 is induced without starvation signals, suggesting that the Tor-Sin3-Rpd3 axis contributes to downregulation of PpAtg32 expression. Moreover, a recent study showed that loss of the Paf1 (RNA polymerase Ⅱ-associated factor 1) complex, a highly conserved complex involved in transcription elongation, leads to global upregulation of ATG genes including ATG32 and ATG11, and induction of mitophagy [36].…”
Section: Transcriptional Activation Of Atg32mentioning
confidence: 99%
“…In cells lacking PpSin3 and PpRpd3, PpAtg32 is induced without starvation signals, suggesting that the Tor-Sin3-Rpd3 axis contributes to downregulation of PpAtg32 expression. Moreover, a recent study showed that loss of the Paf1 (RNA polymerase Ⅱ-associated factor 1) complex, a highly conserved complex involved in transcription elongation, leads to global upregulation of ATG genes including ATG32 and ATG11, and induction of mitophagy [36].…”
Section: Transcriptional Activation Of Atg32mentioning
confidence: 99%
“…For its importance, Atg32 expression and activity are subject to precise complex regulation. At the transcription level, several repressors [ 49 , 50 ] and activators [ 51 , 52 , 53 ] were described to control or link with Atg32 expression. An additional mechanism for conducting mitophagy induction is Atg32 phosphorylation [ 54 , 55 , 56 ].…”
Section: Key Role Of the Atg32 Proteinmentioning
confidence: 99%
“…In both scenarios, the presence of Atg32p is required. Atg32p is constantly present in the outer membrane of the mitochondria and must be phosphorylated by casein kinase 2 (CK2) for mitophagy to be induced [ 50 ]. At present, Atg11 and Atg8 are the only two proteins identified that interact with Atg32p.…”
Section: Future Directionsmentioning
confidence: 99%
“…Additionally, the PAF1C affects Notch, Wnt, and Hedgehog signaling [8,[12][13][14]. The PAF1C has also been reported to regulate the proliferation, differentiation, morphology, cell migration, epidermal morphogenesis, mitophagy, maintenance of stem cells, and tumorigenesis [4,10,[15][16][17][18][19][20][21][22][23]. However, the functional importance of the PAF1C in germ cell development has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%